Comparative Inter- and IntraSpecies Transcriptomics Revealed Key Differential Pathways Associated With Aluminium Stress Tolerance in Lentil - Singh, Chandan Kumar; Singh, Dharmendra; Taunk, Jyoti; Chaudhary, Priya; Tomar, Ram Sewak Singh; Chandra, Shivani; Singh, Deepti; Pal, Madan; Konjengbam, Noren Singh; Singh, M. Premjit; Singh Sengar, Rakesh; Sarker, Ashutosh (Frontiers in Plant Science, 2021)
Aluminium stress causes plant growth retardation and engenders productivity loss under acidic soil conditions. This study accentuates morpho-physiological and molecular bases of aluminium (Al) tolerance within and between wild (ILWL-15) and cultivated (L-4602 and BM-4) lentil species. Morpho-physiological studies revealed better cyto-morphology of tolerant genotypes over sensitive under Al3+ stress conditions. Mitotic lesions were observed in root cells under these conditions. Transcriptome analysis under Al3+ stress revealed 30,158 specifically up-regulated genes in different comparison groups showing contigs between 15,305 and 18,861 bp. In tolerant genotypes, top up-regulated differentially expressed genes (DEGs) were found to be involved in organic acid synthesis and exudation, production of antioxidants, callose synthesis, protein degradation, and phytohormone- and calcium-mediated signalling under stress conditions. DEGs associated with epigenetic regulation and Al3+ sequestration inside vacuole were specifically upregulated in wild and cultivars, respectively. Based on assembled unigenes, an average of 6,645.7 simple sequence repeats (SSRs) and 14,953.7 high-quality single nucleotide polymorphisms (SNPs) were spotted. By quantitative real-time polymerase chain reaction (qRT-PCR), 12 selected genes were validated. Gene ontology (GO) annotation revealed a total of 8,757 GO terms in three categories, viz., molecular, biological, and cellular processes. Kyoto Encyclopaedia of Genes and Genomes pathway scanning also revealed another probable pathway pertaining to metacaspase-1,−4, and −9 for programmed cell death under Al-stress conditions. This investigation reveals key inter- and intraspecies metabolic pathways associated with Al-stress tolerance in lentil species that can be utilised in designing future breeding programmes to improve lentil and related species towards Al3+ stress.